2023
DOI: 10.1039/d3ta00254c
|View full text |Cite
|
Sign up to set email alerts
|

Interphases in aqueous rechargeable zinc metal batteries

Abstract: Despite extensive research efforts in developing aqueous rechargeable zinc metal batteries (RZMBs) as high-energy-density alternatives to both lithium ion and lithium metal batteries, the commercial prospects for RZMBs are still...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…30 It is reported that ZnF 2 possesses high ionic conductivity, which is an effective component in the construction of stable electrode/ electrolyte interface. 31,32 Moreover, the SEM images and XRD patterns of PW and PW-5 wt % ZnO electrodes after 200 cycles were investigated (Figures S7 and S8). PW-5 wt % ZnO exhibits an intact particle without microcracks, as depicted in Figure S7a.…”
Section: Resultsmentioning
confidence: 99%
“…30 It is reported that ZnF 2 possesses high ionic conductivity, which is an effective component in the construction of stable electrode/ electrolyte interface. 31,32 Moreover, the SEM images and XRD patterns of PW and PW-5 wt % ZnO electrodes after 200 cycles were investigated (Figures S7 and S8). PW-5 wt % ZnO exhibits an intact particle without microcracks, as depicted in Figure S7a.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation process of artificial CEIs is often complex, and their stability during the cycling process is rarely mentioned. 35 Based on these facts, it is crucial to construct a stable cathode from bulk phase to surface for advanced AZIBs. To date, there are few effective strategies for this kind of cathode to simultaneously realize bulk-phase structural stability and stable surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The second strategy focuses on kinetically suppressing the electrolysis of electrolytes by fostering the growth of electrolyte interphases on electrodes. [5] This approach takes inspiration from the successful formation of solid electrolyte interphase (SEI) on anodes and cathode electrolyte interphase (CEI) on cathodes in lithium-ion batteries. It is important to note that the names SEI and CEI may not align semantically, potentially confusing newcomers.…”
Section: Introductionmentioning
confidence: 99%